2017
DOI: 10.1186/s12866-017-0961-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Phylogeny, anticancer and antimicrobial potential of fungal endophytes associated with Monarda citriodora L.

Abstract: BackgroundPresent study focuses on diversity and distribution analysis of endophytic fungi associated with different tissues of the Monarda citriodora Cerv. ex Lag. (Lamiaceae/Labiatae). Anticancer and antimicrobial potential of isolated endophytes have also been investigated.ResultsA total of twenty eight fungal endophytes belonging to 11 different genera were isolated from this plant. All the endophytic fungi belonged to the Ascomycota phylum. The leaves were immensely rich in fungal species, while roots sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 53 publications
3
32
0
1
Order By: Relevance
“…Fusarium are a rich source of bioactive compounds (Wang et al, 2011), including ginkgolide B from Ginkgo biloba (Cui et al, 2012), some volatile organic compounds from Brassica napus with antipathogenic activities (Zhang et al, 2014) and some compounds of Monarda citriodora L. with anticancer and antimicrobial activities (Katoch, Phull, Vaid, & Singh, 2017). These findings regarding Fusarium were consistent with Strobel and Daisy (2003) (Revathi, Jeyaseelansenthinath, & Thirumalaikolundhusubramaian, 2004) and may play a role in the protection of the plant against oxidative stress (Torres et al, 2006).…”
Section: Previous Investigations Have Proved That Fungi Of the Genusmentioning
confidence: 79%
See 1 more Smart Citation
“…Fusarium are a rich source of bioactive compounds (Wang et al, 2011), including ginkgolide B from Ginkgo biloba (Cui et al, 2012), some volatile organic compounds from Brassica napus with antipathogenic activities (Zhang et al, 2014) and some compounds of Monarda citriodora L. with anticancer and antimicrobial activities (Katoch, Phull, Vaid, & Singh, 2017). These findings regarding Fusarium were consistent with Strobel and Daisy (2003) (Revathi, Jeyaseelansenthinath, & Thirumalaikolundhusubramaian, 2004) and may play a role in the protection of the plant against oxidative stress (Torres et al, 2006).…”
Section: Previous Investigations Have Proved That Fungi Of the Genusmentioning
confidence: 79%
“…Previous investigations have proved that fungi of the genus Fusarium are a rich source of bioactive compounds (Wang et al, ), including ginkgolide B from Ginkgo biloba (Cui et al, ), some volatile organic compounds from Brassica napus with antipathogenic activities (Zhang et al, ) and some compounds of Monarda citriodora L. with anticancer and antimicrobial activities (Katoch, Phull, Vaid, & Singh, ). These findings regarding Fusarium were consistent with Strobel and Daisy () who reported that Fusarium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Verifying the diversity and enzymatic potential of endophytes from the medicinal plant Bauhinia forficata in Brazil, showed a Shannon-Wiener index value of 1.842 in leaves and 1.677-2.206 in other plant organs (sepals, seeds and stems). Verifying the diversity and anticancer and antimicrobial potential of fungal endophytes associated with the medicinal plant Monarda citriodora in India, Katoch et al (2017) observed an index value of H′ = 2.890 in leaves, while the Fisher-Alpha index did not indicate the presence of diversity. These results indicate that the diversity of endophytic fungi associated with the leaves of M. urundeuva is high and that it is influenced by the ecosystem in which the plant is collected.…”
Section: Discussionmentioning
confidence: 96%
“…As it seems that algae and their endophytic microorganism would be a good source of biologically active secondary metabolites [2] which have long been produced as an adaptation for specific functions in nature [3]. Some researchers have been able to isolate endophytic Cladosporum from different plant and macroalgae [4][5][6][7][8][9][10][11]. Inr this study, endophytes Cladosporium sp.…”
Section: Introductionmentioning
confidence: 99%
“…The use of crude extracts of metabolite compounds produced by Cladosporium sp. has been shown to show anticancer activity [4]. Testing of several bioactive compounds successfully isolated from Cladosporium spp.…”
Section: Introductionmentioning
confidence: 99%